New bryological data from relict mires in the Gran Sasso-Laga National Park (Central Apennines) and their interpretation according to the EUNIS classification and Habitats Directive - Di Pietro,Romeo; Praleskouskaya,Safiya; Aleffi,Michele; Di Pietro,Francesco; Di Pietro,Adriano; TONDI,GIANCARLO; Fortini,Paola (Plant Sociology, 2024)
During a phytosociological field-work campaign aimed at studying some relict Scheuchzerio-Caricetea boreal mires of the montane and subalpine belts of the Laga Mountains, the highest and largest siliceous massif of the Apennine range, several bryophyte taxa of particular biogeographic interest were collected. Among these taxa, Schljakovia kunzeana and Ptychostomum cernuum were found to be new records for the whole Apennine range while Hamatocaulis vernicosus (taxon included in annex II of Habitats Directive) and Scorpidium cossonii as new for the Central-Southern Apennines. Two further species, Bryum canariense, Plagiomnium cuspidatum, were found to be confirmations of old records for the Central Apennines dating back to the early 1900s. At the national and regional level, nine, out of the forty-four bryophyte taxa identified in this study, were found to be new for the Lazio administrative Region, and one taxon as new for the Abruzzo Region. The majority of these new records belong to the boreal chorotype, the Laga Mountains being one of the most important conservation sites for the relict circumboreal and arctic-alpine flora in the whole Mediterranean area. According to both the EUNIS Habitat classification and the EU Habitats Directive Annex I, several, out of the 44 bryophytes identified in this study, act as diagnostic species for European Community Habitats. Nevertheless, a complete correspondence between bryophyte taxon and habitat type was not found upon comparing these two environmental policy systems.